Evaluation of cell death-inducing activity of Monilinia spp. effectors in several plants using a modified TRV expression system - López, Anselmo; van Kan, Jan A. L.; Beenen, Henriek G.; Dolcet-Sanjuan, Ramon; Teixidó, Neus; Torres, Rosario; Vilanova, Laura (Frontiers in Plant Science, 2024)
Brown rot is the most important fungal disease affecting stone fruit and it is mainly caused by Monilinia fructicola, M. laxa and M. fructigena. Monilinia spp. are necrotrophic plant pathogens with the ability to induce plant cell death by the secretion of different phytotoxic molecules, including proteins or metabolites that are collectively referred to as necrotrophic effectors (NEs). We exploited the genomes of M. fructicola, M. laxa and M. fructigena to identify their common group of secreted effector proteins and tested the ability of a selected set of effectors to induce cell death in Nicotiana benthamiana, Solanum lycopersicum and Prunus spp. leaves. Fourteen candidate effector genes of M. fructicola, which displayed high expression during infection, were transiently expressed in plants by agroinfiltration using a modified Tobacco Rattle Virus (TRV)-based expression system. Some, but not all, effectors triggered leaf discoloration or cell death in N. benthamiana and S. lycopersicum, which are non-hosts for Monilinia and in Prunus spp., which are the natural hosts. The effector MFRU_030g00190 induced cell death in almost all Prunus genotypes tested, but not in the Solanaceous plants, while MFRU_014g02060, which is an ortholog to BcNep1, caused necrosis in all plant species tested. This method provides opportunities for screening Prunus germplasm with Monilinia effector proteins, to serve as a tool for identifying genetic loci that confer susceptibility to brown rot disease.